Term neonates with infection and shock display high cortisol precursors despite low levels of normal cortisol. (11th December 2015) - Khashana, Abdelmoneim; Ojaniemi, Marja; Leskinen, Markku; Saarela, Timo; Hallman, Mikko
Abstract: Aim: Neonatal therapy‐resistant septic shock is a common problem in middle and low‐income countries. We investigated whether newborn infants with infection and therapy‐resistant hypotension showed evidence of abnormal levels of cortisol or cortisol precursors. Methods: A total of 60 term or near term neonates with evidence of infection were enrolled after informed consent. Of these, 30 had an infection and refractory shock and 30 had an infection without shock. There were no detectable differences between the groups in the length of gestation, birth weight or gender distribution. Serum was obtained during days four and 14 after birth. Cortisol and cortisol precursor concentrations were analysed using liquid chromatography‐tandem mass spectrometry. Results: The cortisol concentrations were low considering the expected responses to stress and they did not differ between the groups. The infants with infection and shock had higher serum dehydroepiandrosterone (DHEA) levels than those without shock (319.0 ± 110.3 μ g/dL, versus 22.3 ± 18.3 μ g/dL; p < 0.0001) and they also had higher 17‐hydroxy‐pregnenolone, pregnenolone and progesterone concentrations. There were no detectable differences in the levels of 17‐hydroxy‐progesterone, 11‐deoxy‐cortisol, cortisol or cortisone. Conclusion: Septic newborn infants with therapy‐resistant hypotension had very high DHEA levels, suggesting that 3‐beta‐hydroxysteroid dehydrogenase activity limited the rate of cortisol synthesis.